2003
DOI: 10.1364/ao.42.006757
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Broadband N2 Coherent Anti-Stokes Raman Spectroscopy: Comparison of Measurements for Conventional And Modeless Broadband Dye Lasers

Abstract: We have performed high-resolution N2 coherent anti-Stokes Raman spectroscopy (CARS) measurements using a modeless dye laser (MDL) as the Stokes beam source to determine the effects of a reduction in mode noise on the accuracy and precision of the method. These results are compared with previous research that employed a conventional broadband dye laser (CBDL) as the Stokes beam source. A new spectral-fitting procedure was developed to avoid starting-point bias in the least-squares fitting results, which possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…A high-resolution CARS system has been designed to measure in high-speed gas flows and to operate over a 90 -295 K temperature range and a 0.1-5 atm pressure range. 25,26 At ambient conditions, a 10 -15 K standard deviation was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…A high-resolution CARS system has been designed to measure in high-speed gas flows and to operate over a 90 -295 K temperature range and a 0.1-5 atm pressure range. 25,26 At ambient conditions, a 10 -15 K standard deviation was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The instrument precision needs to be carefully characterized, so that fluctuations in the flow can be distinguished from those caused by the instrument. Standard deviation, computed from several singleshot measurements in an oven or a calibration flame, is often used as a metric for the instrument precision [2,18,26,[40][41][42][43][44][45][46]. Commonly reported single-shot temperature standard deviations for N 2 rovibrational CARS are 25-30 K at 300 K [40][41][42]44].…”
Section: Instrument Precisionmentioning
confidence: 99%
“…Vibrational CARS systems with improved precision (10-15 K) at ambient temperature have been developed [18,45,47]. Such systems are characterized by high spectral resolution, and the use of a single mode pump, and modeless Stokes lasers.…”
Section: Instrument Precisionmentioning
confidence: 99%
“…In the years following these experiments, Ewart et al [28] demonstrated that the use of a modeless dye laser was able to reduce, or even eliminate the effect of dye laser mode competition during the generation of experimental CARS spectra, which resulted in improved measurement precision [29]. Nevertheless, the CARS system described here remained capable of producing distributions of referenced database spectra in the High Pressure High Temperature (HPHT) cell with standard deviations of 20 K to 35 K in the 400 K to 700 K temperature range, and 30 K to 45 K in the 700 K to 1,100 K temperature range, for all pressures in the 1.0 bar to 21.0 bar range.…”
Section: The Cars Systemmentioning
confidence: 99%
“…The improvement in CARS measurement precision has developed through improvements to rotational CARS, and the development and use of modeless dye lasers (which removes the spectral noise arising from dye laser mode competition) [28,29]. Of course, this level of precision applies to nearly perfectly heated calibrated environments (calibrated heated cells, and calibrated flames).…”
Section: Introductionmentioning
confidence: 99%